Cooperation in a risky environment: Decisions from experience in a stochastic social dilemma - Florian Artinger; Nadine Fleischhut; M. Vittoria Levati; Jeffrey R. Stevens (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2012)
Often in cooperative situations, many aspects of the decision-making environment are uncertain. We investigate how cooperation is shaped by the way information about risk is presented (from description or from experience) and by differences in risky environments. Drawing on research from risky choice, we compare choices in stochastic social dilemmas to those in lotteries with equivalent levels of risk. Cooperation rates in games vary with different levels of risk across decision situations with the same expected outcomes, thereby mimicking behavior in lotteries. Risk presentation, however, only affected choices in lotteries, not in stochastic games. Process data suggests that people respond less to probabilities in the stochastic social dilemmas than in the lotteries. The findings highlight how an uncertain environment shapes cooperation and call for models of the underlying decision processes.
Keywords: C72; C73; C92; D81; 330; Decisions from Experience; Social Dilemma; Cooperation; Risky Choice; Public Good; Kooperation; Gefangenendilemma; Entscheidung bei Risiko; Öffentliches Gut